Implications for the lithospheric geometry of the Iapetus suture beneath Ireland based on electrical resistivity models from deep-probing magnetotellurics - Rao, C. K.; Jones, Alan G.; Moorkamp, Max; Weckmann, Ute (My University, 2014)
Broad-band and long period magnetotelluric (MT) data were acquired at 39 stations along five NNW-SSE profiles crossing the Iapetus Suture Zone (ISZ) in Ireland. Regional strike analyses indicate that the vast majority of the MT data is consistent with an assumption of a 2-D geo-electric strike direction. Strike is N52°E for the three easternmost profiles and N75°E for the two westernmost profiles; these directions correlate well with the observed predominant geological strike of the study region. 2-D inversions of the galvanic distortion-corrected TE and TM mode data from each profile are shown and discussed. As mapped geological variations between the neighbouring profiles suggest a heterogeneous subsurface, it is important to verify the robustness of the presence and geometries of prominent conductivity anomalies by employing 3-D forward and inverse modelling. A high conductivity layer (resistivity of 1–10 Ωm), found at middle to lower crustal depths and presumed to be indicative of metamorphosed graphitic sediments rich in sulphides deposited during the convergence of the Laurentian and Avalonian continents, essentially constitutes the electrical signature of the ISZ. Shallow conductors observed are probably due to black shales that were widely deposited within the sedimentary accretionary wedge during Ordovician time. We interpret the moderately low resistivity at shallow depths from west to east across Ireland as indicative of an increase in maturity of the black shales in the easterly direction. From our conductivity models the southern extent of the ISZ is inferred to lie between the Navan Silvermines Fault and the Navan Tipperary Line, and shows clear resistivity contrast along all the profiles at the southern MT stations. The change in resistivity deduced from the 2-D models is spatially related to the composition of Lower Palaeozoic Ordovician, Silurian, Devonian and Carboniferous rocks. At upper mantle depths of about 60 km, a high conductivity block below the central MT stations is found to lie within the accretionary wedge of the Iapetus suture, and the location of the conductive anomaly corroborates reasonably well with the inferred spreading head of the putative Iceland plume-related magmatic intrusion. The low resistivity upper crust beneath the ISZ is indeed rich in Ordovician rocks with black shale content in the eastern as well as the central part; the western part is largely underlain by a highly resistive block of volcanic and metamorphosed rocks forming crystalline basement.
Keywords: Electrical properties; Magnetotellurics; Continental crust; Continental margins; Convergent; Crustal structure; Europe; Electrical resistivity models